Keterlaksanaan Pembelajaran PJOK Tingkat Sekolah Dasar di Masa Pandemi Covid 19 Kota Kupang - Yusuf Nikodemus Lopo; Wasis Djoko Dwiyogo; Roesdiyanto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to determine the implementation of PJOK learning at the elementary school level during the COVID-19 pandemic in Kupang City. The method in this research is qualitative, using purposive sampling and snowball sampling. The results of his research show that the PJOK learning planning at the elementary school level during the covid-19 pandemic for teachers throughout the city of Kupang is adjusted to the PJOK elementary school curriculum and also adapted to online learning. The implementation of PJOK learning at the elementary school level during the covid-19 pandemic for teachers throughout the city of Kupang is in accordance with the lesson plan that has been made. Evaluation of PJOK learning at the elementary school level during the covid-19 pandemic for teachers throughout the city of Kupang uses affective, cognitive and psychomotor assessments. For students they are not happy with learning PJOK online but they always do the assignments from the teacher. Parents always help children when learning PJOK from home. The conclusion is that the implementation of PJOK learning during the covid 19 pandemic for teachers, students and parents has been carried out but there are still obstacles.